(untitled) (Plant Tissue Culture and Biotechnology, 2008)
An in vitro experiment with two cultivars, Mahon Demias and Hidhab of bread wheat (Triticum aestivum L.) exhibited appreciable callus induction but differed significantly in the capacity of calli proliferation and regeneration under salinity stress; even though Mahon Demias appeared relatively more tolerant than Hidhab. The results indicated the need to optimize a robust protocol for callus induction, maintenance and regeneration before selection process for tolerance to salinity is embarked upon. Key words: Bread wheat, Salinity stress, Callus proliferation, Mature embryo DOI = 10.3329/ptcb.v17i1.1117 Plant Tissue Cult. & Biotech. 17(1): 19-27, 2007 (June)